EVALUATION OF MEVLANA'S THOUGHTS IN THE CONTEXT OF COGNITIVE THERAPY - MEHMET AK (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
In the works of Mevlana (Rumi), the social, religious and philosophical dimensions of human life were examined and the psychological aspects as well. The cognitive behavioral therapies are among the most commonly usedtherapy methods and also the most studied ones in the literature. According to the this model, the person can distorte the objective state by the present cognitive substructure. As a result of these distortions, the automatic thinkings arises which lead to the emergence of a number of dysfunctional emotions and often behaviors associated with these emotions. Spontaneously occured automatic thoughts, related to problematic behaviors or disturbing emotions are accepted without any hesitations are existed at the top of the mind. In the cognitive therapy, it is suggested that the focus of the therapy should be the individual's thoughts and beliefs, because some individuals may have the potential to destroy-reduce other¸s experiences with their ability to influence them with their own experiences. Mevlana's books emphasized that the relationship between thoughts and feelings, and also included a lotsof recommendations that suggest awareness and cognitive changes to get rid of various mental problems. In this rewiev, the aim was to examine the Mevlana's approach to thought in the context of cognitive therapy. The main books of Mevlana; Mesnevi, Fihi-Ma-Fih and Divan-i Kebir were examined and discussed in the sections related to thought. [JCBPR 2017; 6(2.000): 82-87]